2017
DOI: 10.1111/bor.12262
|View full text |Cite
|
Sign up to set email alerts
|

High‐latitude vegetation and climate changes during the Mid‐Pleistocene Transition inferred from a palynological record from Lake El'gygytgyn, NE Russian Arctic

Abstract: A continuous pollen record from Lake El'gygytgyn (northeastern Russian Arctic) provides detailed information concerning the regional vegetation and climate history during the Mid‐Pleistocene Transition (MPT), between 1091 ka (end of Marine Isotope Stage (MIS) 32) and 715 ka (end of MIS 18). Pollen‐based qualitative vegetation reconstruction along with biome reconstruction indicate that the interglacial regional vegetation history during the MPT is characterized by a gradual replacement of forest and shrub vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Cold steppe biome scores in the pollen record significantly increased from this point in time onwards indicating accelerated aridification. The long-term cooling and aridification trend observed in the El'gygytgyn record corresponds with global ice-sheet expansion, sea-level lowering, coast-line shifts, shelf exposure and an intensified Siberian High and is considered additionally strengthened by the Tibetan Plateau uplift (Zhao et al, 2018).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Cold steppe biome scores in the pollen record significantly increased from this point in time onwards indicating accelerated aridification. The long-term cooling and aridification trend observed in the El'gygytgyn record corresponds with global ice-sheet expansion, sea-level lowering, coast-line shifts, shelf exposure and an intensified Siberian High and is considered additionally strengthened by the Tibetan Plateau uplift (Zhao et al, 2018).…”
Section: Discussionmentioning
confidence: 84%
“…Prior to the EMPT, the amplitude of climate fluctuations was smaller and the duration of climate cycles was shorter, which possibly resulted, in West Beringia, in relatively dry, cool but more moderate climate that became progressively colder in the course of the EMPT but remained more stable than in other parts of the Holarctic. The palynological record from the composite sediment core of Lake El'gygytgyn, ICPD Site 5,011-1, about 467 km SE of the Cherskiy Ovrag provides valuable information on the regional history of vegetation and climate in West Beringia over the EMPT interval, i.e., between 1,091 and 715 kyr (Zhao et al, 2018). The pollen data indicate shrub tundra and cold steppe communities alternatingly dominating over the major part of the studied Early Olyorian period until MIS 24 (from 1,091 until 930 kyr) with Poaceae, Cyperaceae and Artemisia pollen and high contents of Selaginella rupestris spores prevailing during cold phases and increased amounts of Betula and Alnus (shrub birch and shrub alder) with sporadic occurrences of Larix during warm stages.…”
Section: Discussionmentioning
confidence: 99%
“…Pollen assemblages of PZ III in section 118 (Figure 3) are dominated by Betula, Alnus and Pinus. In the El'gygytgyn pollen record (e.g., Lozhkin et al, 2007Lozhkin et al, , 2017Matrosova, 2009;Andreev et al, 2014;Zhao et al, 2018Zhao et al, , 2019, similar pollen assemblages have only been reported from the Late Pleistocene. During PZ III of section 118, larch forests with stone pines, shrub alders, dwarf birches, and ericaceous low shrubs in underbrush dominated the vegetation cover.…”
Section: Upper Pleistocenementioning
confidence: 83%
“…) and during the mid‐Pleistocene Transition (Zhao et al . ). These studies also synthesized Arctic vegetation dynamics and corresponding orbital settings during different interglacials.…”
Section: Discussion and Interpretationmentioning
confidence: 97%